2011
DOI: 10.1063/1.3573668
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on the combined effects of nanotube shape and shear flow on the electrical percolation thresholds of carbon nanotube/polymer composites

Abstract: Here we investigate the combined effects of carbon nanotube (CNT) properties such as aspect ratio, curvature, and tunneling length and shear rate on the microstructure and electrical conductivities of CNT/polymer composites using fiber-level simulations. Electrical conductivities are calculated using a resistor network algorithm. Results for percolation thresholds in static systems agree with predictions and experimental measurements. We show that imposed shear flow can decrease the electrical percolation thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…29,62 However, the completely uniform dispersion of nanorods will decrease its conductivity because of the large inter-filler distance, and theoretically the presence of partially aggregated filler can result in 6 For the nanorods with high aspect ratio, there is a tendency for nanorods agglomeration 30 , which is consistent with our results. 29,62 However, the completely uniform dispersion of nanorods will decrease its conductivity because of the large inter-filler distance, and theoretically the presence of partially aggregated filler can result in 6 For the nanorods with high aspect ratio, there is a tendency for nanorods agglomeration 30 , which is consistent with our results.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 86%
See 1 more Smart Citation
“…29,62 However, the completely uniform dispersion of nanorods will decrease its conductivity because of the large inter-filler distance, and theoretically the presence of partially aggregated filler can result in 6 For the nanorods with high aspect ratio, there is a tendency for nanorods agglomeration 30 , which is consistent with our results. 29,62 However, the completely uniform dispersion of nanorods will decrease its conductivity because of the large inter-filler distance, and theoretically the presence of partially aggregated filler can result in 6 For the nanorods with high aspect ratio, there is a tendency for nanorods agglomeration 30 , which is consistent with our results.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 86%
“…23 A partially aligned nanotube film can induce the minimum resistivity and the location of resistivity minimum depends on the nanotube length and device length. 29 Furthermore, high aspect ratio nanotubes are not as easily dispersed and aligned in the flow direction with shear stress as low aspect ratio nanotubes. 27 And an agglomerated structure is beneficial for high electrical conductivity.…”
mentioning
confidence: 99%
“…, SWNT, MWNT, and vapor-grown carbon nano-fibers (VGCNF), as well as layered graphitic materials). This disappointment has led to a decline in the hype surrounding such composites and a shift of research focus to some of the other unique features of these materials such as their electrical [57,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93], thermal [57,68,73,76,86,94,95,96,97,98,99,100,101,102,103], and optical properties [104,105,106,107,108,109]. This rise and fall of interest in polymer nano-composite research is analogous to what happened between 1832 and 1939 when polymers were originally discovered but not well understood [110,111].…”
Section: Micro-structural Development In Polymer/cnt Fibersmentioning
confidence: 99%
“…The values of electrical conductivity can be determined from generated microstructures using a resistor network algorithm. It has been shown that if a weak shear flow is applied to a viscous fiber suspension, the electric percolation threshold decreases due to shear-induced formation of conductive aggregates [30]. Increasing shear rate has a negative effect on conductive network formation: when shear rate exceeds a critical value the electrical conductivity was found to decrease to the matrix conductivity [31].…”
mentioning
confidence: 99%
“…Similar to other percolation theories, this newest approach lacks information on time -and shear-dependence of resistor conductivity. A very promising numerical approach to the electrical conductivity of static and sheared CNT/polymer suspensions has been reported recently by Eken et al [30,31]. Composite microstructures were generated using a fiber-level simulation method, in which monodisperse fibers (carbon nanotubes) are modeled as a sequence of connected rigid cylinders.…”
mentioning
confidence: 99%